The relationship between self-efficacy and self-management in post stroke patients at Home Stroke Rehabilitation Malang - Nur Safitri Hazanah; Siti Ainun Marufa; Atika Yulianti (Physical Therapy Journal of Indonesia, 2023)
Background: Stroke is a neurological disorder characterized by blockage of blood vessels. The effects of stroke cause problems with motor, sensory and cognitive functions. These problems result in patients often complaining and feeling useless, so patients experience a decrease in self-efficacy. Low self-efficacy will cause a low level of self-acceptance and motivation that affects the patient's confidence in performing functional activities and self-management related to the healing process in stroke patients. Objective: This study aimed to analyze the relationship between self-efficacy and self-management in stroke patients. Methods: The research design used a cross-sectional study method conducted in December 2022 with a population of all stroke patients at Home Stroke Rehabilitation Malang who met the criteria to become participants in this study. Measurement of self-efficacy using The Stroke Self Efficacy Quetionnaire (SSEQ) and self-management using The Southampton Stroke Self Management Quetionnaire (SSSMQ). Rank Spearman was used to determining the relationship between the two variables showed that out of 49 respondents, there was a relationship between self-efficacy and self-management using the Rank Spearman test. Results: The study’s result (p = 0.000, r = 0.949) shows a very strong correlation. It can be concluded that there is a very strong relationship between self-efficacy and self-management in stroke patients because high confidence is very influential on the actions or attitudes of patients so that patients can move and prevent recurrent strokes and carry out rehabilitation programs properly. Conclusion: The higher the self-efficacy, the higher the self-management in post-stroke patients and vice versa. These two crucial components will affect the rehabilitation phase of post-stroke patients.